Structure of the pork value chain in Northern Uganda: implications for Taenia solium control interventions - Ngwili, Nicholas; Ahimbisibwe, Salaviriuse; Sentamu, Derrick Noah; Thomas, Lian F.; Ouma, Emily (Frontiers in Veterinary Science, 2023)
This study characterises the pork value chain in Agago, Kitgum, Lamwo, and Pader districts of Northern Uganda and analyses its implications on the transmission and control of Taenia solium infections. Data were collected through focus group discussions (FGDs) with farmers and pig and pork traders, key informant interviews (KIIs) with local government officials and consumers, and district-level multi-stakeholder mini workshops organised in the study area. The value chain actors identified include input and services providers, pig farmers, live pig traders, pork traders, and consumers. Most of the pig production, marketing and consumption was found to occur through informal channels. Pig production in this area is dominated by smallholder extensive systems, with most producers keeping less than 10 pigs. The production segment of the pig value chain is characterized by low use of inputs and services such as veterinary extension, drugs and improved feeds. Pigs scavenge for food under free-range systems and are at risk of parasitic infections such as the zoonotic helminth Taenia solium. This risk is exacerbated by the inherent contextual aspects of the study sites including low latrine coverage, open defecation, and high poverty. In addition, some respondents viewed pigs as “sanitation policemen” where they leave them to roam around and eat dirt including feaces thereby cleaning the environment. T. solium was recognised as an important pig health constraint in this value chain alongside African swine fever (ASF). Unlike ASF that was associated with the pig mortalities, the cysts were associated with rejection of pigs by traders at purchase, condemnation of pig carcasses by meat inspectors and rejection of raw pork by consumers at points of sale. Poor organisation of the value chain and lack veterinary extension and meat inspection services results in some pigs infected with T. solium entering the food chain, exposing consumers to infection with the parasite. To reduce the pig production losses and public health impact from T. solium infections, there is need for control and prevention interventions targeting specific nodes of the value chain where the risk of transmission is highest.